Proceedings of the 2009 ACM Symposium on Applied Computing 2009
DOI: 10.1145/1529282.1529670
|View full text |Cite
|
Sign up to set email alerts
|

A session based personalized search using an ontological user profile

Abstract: Within the information overload on the web and the diversity of the user interests, it is increasingly difficult for search engines to satisfy the user information needs. Personalized search tackles this problem by considering the user profile during the search. This paper describes a personalized search approach involving a semantic graph-based user profile issued from ontology. User profile refers to the user interest in a specific search session defined as a sequence of related queries. It is built using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 5 publications
0
51
0
3
Order By: Relevance
“…Our main focus of this paper is to analyse the usefulness of the user's recent browsing history for query suggestions which will allow us to create a personal profile for each user and use that profile when ranking query suggestions. Personalized search, in general attracted attention of a lot of researchers, [18,19,20,21,22]. Each and every study showed that user's personal query history is very important in search systems.…”
Section: Related Workmentioning
confidence: 99%
“…Our main focus of this paper is to analyse the usefulness of the user's recent browsing history for query suggestions which will allow us to create a personal profile for each user and use that profile when ranking query suggestions. Personalized search, in general attracted attention of a lot of researchers, [18,19,20,21,22]. Each and every study showed that user's personal query history is very important in search systems.…”
Section: Related Workmentioning
confidence: 99%
“…There are attempts to employ semantics description languages for representation of interested fellows' profiles. In [26], there is described a personalized search approach involving a semantic graph-based interested fellow's profile issued from ontology. Interested fellow's profile refers to her interest in a specific search session.…”
Section: Postprocessingmentioning
confidence: 99%
“…The directory structure of the Open Directory Project (ODP 7 ) is used as basis. Also in (Daoud et al, 2009) ODP is used for building a graph based user profile to improve search results during a search session. In (Gauch et al, 2003) a user profile is a weighted concept hierarchy based on a reference ontology.…”
Section: Related Workmentioning
confidence: 99%